Harnessing Forests as Pathways to Prosperity in Liberia : Policy Note - World Bank (World Bank, Washington, DC, 2021)
Liberia is the most forested country in West Africa, with more than two thirds of its land surface covered by forest. In 2019, 47.5 percent of the Liberian households (HHs) lived in proximity to and were significantly dependent on the country’s forests. Results from the recent sample-based National Household Forest Survey (NHFS 2019) conducted in these forest-proximate areas reveal a high dependence on forest products both for direct consumption and as a source of income. These forest products, ranging from fuelwood to medicinal plants, also provide HHs with an important social safety net during natural and economic shocks and crises, such as the Coronavirus (COVID-19) pandemic. At the same time, Liberia is one of the world’s poorest countries. The NHFS found that the average income for these forest proximate HHs which is substantially below the country’s average annual HH income. This points to the need to maximize the potential of forests for poverty reduction in a sustainable manner. Using the data collected from the recent NHFS, this policy note unpacks the HH and forest interactions, for forest-proximate HHs. The note: (1) identifies the sources within forestry and other sectors from which HHs derive their subsistence and income needs; (2) looks at the income generating potential of various activities that a HH participates in and its labor time allocation; and (3) highlights the gender aspects of poverty, particularly as they relate to the forestry sector.